Devastating complications of intravenous line/drugs extravasation in hand - Maharaj, Ramesh Chandra; Sethy, Ram Chandra; Chand, Dillip Kumar; Mishra, Nihar Ranjan; Panigrahi, Sibasish (International Journal of Research in Orthopaedics, 2018)
Background: Peripheral intravenous (IV) line insertion for treatment purpose is a common practice and a very simple procedure in hospitals undertaken worldwide. These intravascular lines are crucial in resuscitation, allow vital medication to be administrated, and can be used to monitor the patients vital parameters. Thus the complications due to it like phlebitis, leaking or extravasation are usually we come across. This study reviews some serious complications of peripheral intravenous infusion in hand and discusses the treatment approaches and its an endeavour to provide information regarding healthy practise of IV line insertion, recognising complications at the earliest and treat them accordingly. Methods: In our study, we have received 30 cases with devastating complications due to post IV line extravasation in hand in which most of them intervened surgically. Though these complications most of the time subside of its own for which these are frequently underestimated but sometimes there may be serious enough to endanger the limb at risk and threaten the life with devasting complications like septicaemia. Results: In our series, we have got abscess or necrotising fasciitis in (17%), compartment syndrome with VIC (10%), Gangrene (13%), cellulitis (30%), non-healing ulcer (20%), suppurative thrmbophlebitis (10%) etc. Conclusions: Hence, this study should encourage the health personnel to have good knowledge about the drug to be used, to practice healthy technique of IV line insertion, to diagnose the complication if any, at a earliest possible time and if the complication is already established, then they should not hesitate to take the help of proper speciality dealing with hand.